2012
DOI: 10.1111/j.1600-6143.2011.03892.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model of CMV Transmission Following Kidney Transplantation

Abstract: Reactivation of latent CMV in transplant recipients remains a significant infectious complication of transplantation. Investigation of the cellular and molecular mechanisms by which reactivation occurs has been hampered by the lack of appropriate animal models. Here, we show that transplantation of kidneys latently infected with murine cytomegalovirus (MCMV) into NOD.Cg-Prkdc scid IL2rg tm1Wjl /Szj mice results in reactivation of latent virus in the kidney, resulting in a disseminated primary infection of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…A new model for reactivation of infectious virus in genetically immunodeficient transplant recipients has recently been described [85]. As in the previous model, activation of transcription factors that bind to the ie promoter and reactivation of ie gene expression was detectable within two days after transplant (unpublished observations), but unlike the allogeneic transplant model, reactivation of infectious virus becomes detectable in immunodeficient recipients over a period of weeks.…”
Section: Reactivation Of Latent CMVmentioning
confidence: 99%
See 2 more Smart Citations
“…A new model for reactivation of infectious virus in genetically immunodeficient transplant recipients has recently been described [85]. As in the previous model, activation of transcription factors that bind to the ie promoter and reactivation of ie gene expression was detectable within two days after transplant (unpublished observations), but unlike the allogeneic transplant model, reactivation of infectious virus becomes detectable in immunodeficient recipients over a period of weeks.…”
Section: Reactivation Of Latent CMVmentioning
confidence: 99%
“…This was likely due to the very slow rate of CMV replication combined with the rapid rejection that occurs when allogeneic organs are transplanted into immunocompetent mice. Subsequent studies showed that reactivation of infectious virus in the donor kidney, and spread of the virus to recipient organs, could be induced by transplanting latently infected kidneys into immunodeficient recipient mice [85]. …”
Section: Reactivation Of Latent CMVmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh tissue was finely minced on ice, and the chromatin was fixed in 1 % formaldehyde as previously described (Liu et al, 2008(Liu et al, , 2010, and frozen in liquid nitrogen. Due to the very low MCMV DNA copy number in kidneys of latent mice [*1 copy of MCMV DNA per 10 000 cellular genomes (Li et al, 2012)] and the large amount of chromatin required for each ChIP, chromatin from 5-6 kidneys was pooled for each antibody. Frozen pellets of fixed tissue from 30-50 transplants were resuspended in hypotonic lysis buffer, and processed for immunoprecipitation as previously described (Liu et al, 2008(Liu et al, , 2010.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies have used the mouse kidney transplant model to investigate the effect of transplant‐associated viral infections . In mice infected with polyomavirus the allograft developed worse histological injury with increased numbers of CD8+ T cells compared with virus‐free recipients .…”
Section: Resultsmentioning
confidence: 99%